Adoptive transfer of protection against Trypanosoma cruzi with lymphocytes and macrophages. - Burgess, D E (1979)
Female C57BL/6J mice were infected with Trypanosoma cruzi and subsequently given macrophages or lymphocytes from syngeneic donors which had recovered from the acute infection. Mice which received immune peritoneal macrophages, splenic lymphocytes, or lymph node lymphocytes developed lower mean parasitemias and cumulative mortalities than did recipients of nonimmune cells. Neither peritoneal lymphocytes nor splenic macrophages were protective, however. These studies indicate that splenic and lymph node lymphocytes are effective in transferring protection against T. cruzi, whereas the macrophage is somewhat less effective.